Hepatocellular Carcinoma with Inferior Vena Cava and Right Atrium Tumor Thrombus - Gunasekaran, Arun Kumar; Malviya, Amit; Ete, Tony; Mishra, Animesh; Barman, Bhupen; Jamil, Md; Lynser, Donboklang (Acta medica Lituanica, 2021)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer and cancer related deaths worldwide. Metastasis of HCC into the cardiac cavity is mostly caused by direct tumor thrombus invasion through the major hepatic veins and of vena cava inferior with continuous extension into the right cardiac cavity. Right heart metastasis without invasion of inferior vena cava (IVC), which may be caused by haematogenous spread of cancer cells, is rarely reported. We report a case of HCC with IVC and right atrium (RA) thrombus in a patient who presented to us with decompensated cardiac failure. Strikingly, the patient was young and with negative serum HBsAg, and anti-HCV results. Our case highlights a rare presentation of metastatic intracardiac tumor thrombus involving the RA in advanced HCC without any symptoms of cardiac failure, and henceforth, the role of screening echocardiography for all patients with advanced HCC especially with vena caval involvement to rule out intracardiac thrombus.